Corrosion Inhibition Effect of Dicycloimine Hydrochloride (DCI) on Mild Steel in 1M HCl - R. Rajalakshmi; S. Subhashini (E-Journal of Chemistry)
Addition of corrosion inhibitors is one of the widely used methods to control corrosion. In this work, an attempt has been made to explore the possibility of using dicycloimine hydrochloride (DCI) as an inhibitor on mild steel in 1 M HCl. The inhibition efficiency of DCI has been evaluated by conventional weight loss method and electrochemical polarization studies. Experimental results are fitted to various adsorption isotherms. Thermodynamic parameters have also been studied from temperature studies. The results reveal that DCI acts as an effective inhibitor (around 90% of IE) in HCl media.